Death and the Pearl Maiden Plague, Poetry, England - Coley, David K. (The Ohio State University Press, 2019)
Shows how English responses to the Black Death were hidden in plain sight-as seen in the Pearl, Cleanness, Patience, and Sir Gawain and the Green Knight poems.